2017
DOI: 10.4244/eij-d-15-00408
|View full text |Cite
|
Sign up to set email alerts
|

Selective use of contemporary drug-eluting stents in primary angioplasty for ST-elevation myocardial infarction: pooled analysis of COMFORTABLE AMI and EXAMINATION

Abstract: Aims: Selective use of DES only in patients at higher risk of MACE is common practice, particularly in healthcare systems with a large premium payable for DES. We aimed to identify subgroups of patients in which the use of BMS in primary percutaneous coronary intervention (PPCI) for STEMI can still be justified.Methods and results: We performed a patient-level pooled analysis of COMFORTABLE AMI and EXAMINATION comparing contemporary DES with BMS in PPCI. A risk score was applied using three parameters: lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The lower tendency of use of DESs in the low-SES group observed in our study has also been reported in American cohorts ( 30 32 ), which is a “treatment-risk paradox” in which higher-risk patients are not treated with optimal or evidence-based strategies, and the use of mechanical support devices is reduced, and it may result in prognosis worsening ( 19 , 33 , 34 ). This finding may reflect the fact that differences in outcomes may not only be related to the use of a specific treatment/device in the acute period but to a whole standardized medical approach in which access to secondary prevention may be of utmost importance ( 35 ) and that the health system may override the burden of higher risk subsets.…”
Section: Discussionsupporting
confidence: 82%
“…The lower tendency of use of DESs in the low-SES group observed in our study has also been reported in American cohorts ( 30 32 ), which is a “treatment-risk paradox” in which higher-risk patients are not treated with optimal or evidence-based strategies, and the use of mechanical support devices is reduced, and it may result in prognosis worsening ( 19 , 33 , 34 ). This finding may reflect the fact that differences in outcomes may not only be related to the use of a specific treatment/device in the acute period but to a whole standardized medical approach in which access to secondary prevention may be of utmost importance ( 35 ) and that the health system may override the burden of higher risk subsets.…”
Section: Discussionsupporting
confidence: 82%